Social policies and adaptation to extreme weather: Evidence from South Africa - Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
Can social policies assist households in coping with the effects of extreme weather events? We evaluate the role of the Indigent Program, an income-based social assistance program in South Africa that provided free electricity and water to poor households, in helping rural households adapt to drought conditions, using household-level panel data. We first analyse the impact of eligibility for the program on the likelihood of acquiring access to electricity and piped water, as well as on expenditure on these amenities, and find that program eligibility did not have a significant impact on these measures. While eligibility for the program was largely ineffective in increasing appliance adoption, electricity use, or welfare, we find that eligible households were more likely to use a borehole as their main water source, a result primarily driven by drought-affected households, suggesting a possible adaptation response facilitated by the program. In general, the benefits offered by the program may have only been marginal in facilitating significant adaptation responses, exacerbated by the fact that households in droughtaffected areas may not have enough assets/wealth to purchase durables, or to make complementary investments. Policy implications relate to the effective design of policies to enable access and use of amenities such as electricity and water, and easing access to credit to facilitate adaptation responses, as climatic conditions intensify.
Keywords: O13; Q01; Q54; 330; Adaptation; Social policies; Electricity; Water; Droughts; Impact evaluation; South Africa